(4u-3)/5=4-((7u-2)/4)

Simple and best practice solution for (4u-3)/5=4-((7u-2)/4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4u-3)/5=4-((7u-2)/4) equation:


u in (-oo:+oo)

(4*u-3)/5 = 4-((7*u-2)/4) // - 4-((7*u-2)/4)

(4*u-3)/5+(7*u-2)/4-4 = 0

(4*(4*u-3))/(4*5)+(5*(7*u-2))/(4*5)+(-4*4*5)/(4*5) = 0

4*(4*u-3)+5*(7*u-2)-4*4*5 = 0

51*u-80-22 = 0

51*u-102 = 0

(51*u-102)/(4*5) = 0

(51*u-102)/(4*5) = 0 // * 4*5

51*u-102 = 0

51*u-102 = 0 // + 102

51*u = 102 // : 51

u = 102/51

u = 2

u = 2

See similar equations:

| 4x+2x-x+3x= | | (7-3)2+3(8)= | | (4f+13g)(2w)= | | 7/2x-5=4/x+1 | | (4v-4)/3=((v+1)/6)+2 | | =x^2+22x+72 | | 11+21(11)=(13+c)13 | | 12y-10=-11+9y | | 3(x-6)/4=4x+6 | | 3(2n+1)+4(n-2)= | | h/2+7=10 | | 1=n/4-1 | | 20=5x+7x^2 | | 14=9-p | | 2+x/5=0 | | 4+b/-2=-2 | | 0=14d+8d^2 | | (6+y)(2y+5)=0 | | 12x+15=5x+62 | | 5x+x-4=-4 | | 2/3x-1/2y=12 | | (6x-4)-(2x+5)= | | 2/10=b/5 | | Y-12X+4Y+16=0 | | (13a+9b)-(2a-4b)= | | -2(w+4)=2w-24 | | 4y+3=-21 | | 72=9y+36 | | 4(-x-2)+3=15 | | -(-6x+5)=-(x+5) | | (9+7i)/(-10+8i) | | -1+m=-7 |

Equations solver categories